Inflammation, Frailty and Cardiovascular Disease - SOYSAL, PINAR; SOYSAL, PINAR; Arik, Ferhat; Smith, Lee; Jackson, Sarah E.; IŞIK, AHMET TURAN (My University, 2020)
Chronic inflammation, which is called -inflamm-aging-, is characterized by an increased level of inflammatory cytokines in response to physiological and environmental stressors, and causes the immune system to function consistently at a low level, even though it is not effective. Possible causes of inflammaging include genetic susceptibility, visceral obesity, changes in gut microbiota and permeability, chronic infections and cellular senescence. Inflammation has a role in the development of many age-related diseases, such as frailty. Low grade chronic inflammation can also increase the risk of atherosclerosis and insulin resistance which are the leading mechanisms in the development of cardiovascular diseases (CVD). As it is well known that the risk of CVD is higher in older people with frailty and the risk of frailty is higher in patients with CVD, there may be relationship between inflammation and the development of CVD and frailty. Therefore, this important issue will be discussed in this chapter.